Transposição ovariana por videolaparoscopia em cadáver de feto humano - Oliveira Filho, Manoel (2004)
Objectives: Videoendoscopic surgery began at the end of twentieth century as a great innovation however; only in recent years its potential role has been explored. The endoscopes have been used to carry out a variety of diagnosis and therapeutic procedures. The acquisition of knowledge and habilities required by the technique obligates both the inexperienced surgeon and the experienced one, to seek information, training, qualification, and accreditation on new operative method in order to practice present time surgical medicine. Minimum access endoscopic surgery had an outstanding expansion on its applications for the past 10 (ten) years; due to this the Videoendoscopic is not totally defined within the oncologic gynecology. The preservation of ovarian function on young women that have precocious stage uterine colon cancer, Hodgkin lymphoma, Non-Hodgkin lymphoma and colon carcinoma – rectal that requires external and internal radiotherapy, the Videoendoscopic has been used as a surgical method in order to minimize the radiation effects, because it is a safe and effective procedure to preserve the ovarian function. The purpose of this work was to transpose the ovaries in human corpse fetus to outside the pelvic region and replace them in the highest possible point on the abdomen sidewall. Methods: Videolaparoscopic fixation of the ovaries with purse-string suture and clips. Two 18.9 in. (48cm) and 19.7 in (50cm), weighting 6.8 and 7.3 pounds (3.1 and 3.3 (kilograms) respectively, human fetus corpses were used. All the equipments and Videoendoscopic surgery instruments were used The usage of human material as a way of training provided the activity the possibility to carry out in similar conditions and of identical anatomy, whenever coming across surgery with alive individuals. Conclusion: the purpose of this work represents a perfectly feasible method of carrying out, training practice importance and surgeon improvement for the ovarian function preservation.